O tempo das canhoneiras: organização e atuação dos navios de guerra nos rios amazônicos - Pablo Nunes Pereira; Joana D’Arc Moreira da Silva (Navigator)
This work intends to discuss about the organization of the warships in the Amazon Flotilla and the actings of those ships between the second half of the nineteenth century and the first decades of the twentieth century. We propose to consider three generations of warships designated to the region: the gunboats used in the War of Paraguai (decades of 1850 and 1860), those build after the War (decades of 1870 to 1890) and the fluvial gunboats of the modernization process discussed by the naval programs of 1904 and 1906. About the acting of those ships, we discuss the hull question of the boats and the relations with problems involving the tele-graphs and also the operations executed using as an example the Guarany gunboat at the Amapá question.